2017
DOI: 10.1016/j.actatropica.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Larval stress alters dengue virus susceptibility in Aedes aegypti (L.) adult females

Abstract: In addition to genetic history, environmental conditions during larval stages are critical to the development, success and phenotypic fate of the Aedes aegypti mosquito. In particular, previous studies have shown a strong genotype-by-environment component to adult mosquito body size in response to optimal vs stressed larval conditions. Here, we expand upon those results by investigating the effects of larval-stage crowding and nutritional limitation on the susceptibility of a recent field isolate of Aedes aegy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
(47 reference statements)
2
23
0
Order By: Relevance
“…Three studies examined the effects of larval competition on dengue vector competence [142,143,172]. Bara et al [142] found that Ae.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies examined the effects of larval competition on dengue vector competence [142,143,172]. Bara et al [142] found that Ae.…”
Section: Resultsmentioning
confidence: 99%
“…albopictus larval competition resulted in significantly longer development times, lower emergence rates, and smaller adults, but did not significantly affect the extrinsic incubation period of DENV-2 virus. Kang et al [172] found that larval-stage crowding and nutritional limitation led to lower survival rates until pupation, lower blood feeding success, slower development, smaller adult body size, and lower susceptibility to DENV-2 infection. Four studies examined a variety of blood meal characteristics on arboviral infection rate [122,123,147,173].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dengue, chikungunya and zika are all transmitted by the same vector, Aedes aegypti mosquito [8,10,[14][15] . Because there are still no validated vaccines against dengue or a specific antiviral for treatment of those diseases [16][17][18] , the best control method is prevention, by attacking its vector [19] . Vector control is done by eliminating propitious locations for oviposition or by fighting these mosquito larvae.…”
Section: Introductionmentioning
confidence: 99%